MEMBANGUN CITRA PUBLIK DALAM LEMBAGA PENDIDIKAN ISLAM - Indrioko, Erwin (IAIN Kediri, 2015)
Image is a term from the world of industry that is currently entered in the education world, especially the Islamic educational institutions. Today the business is very important imaging in the presence of Islamic educational institutions, this is due to the more important and urgent to establish the image of Islamic educational institutions in response to his role in educating generations of the nation, especially in the framework of the unitary republik of Indonesia. Deterioration of Islamic educational institutions which initially marginal in national policy has come for Islamic educational institutions took part in the arena of educating generations of struggle to give birth to a quality educational institutions in the ministry.Keywords; opini publik, pencitraan, madrasah, mutu pendidikan